2023
DOI: 10.1155/2023/8690464
|View full text |Cite
|
Sign up to set email alerts
|

Seed-Borne Fungi Associated with Diverse Rice Varieties Cultivated in the Western North Region of Ghana

Abstract: Rice is a major staple in the Ghanaian diet. However, its production is constrained by fungal diseases. A survey was conducted in 2018 in three selected districts in the Western North Region of Ghana using a structured questionnaire and face-to-face interaction with 230 farmers to assess their knowledge, perceptions of seed-borne fungal diseases, and management practices. Additionally, fungi associated with farmer’s seeds were isolated and identified through the Agar and Blotter tests. Findings indicate that 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Rhizoctonia solani can survive for extended periods in the soil, and infected plant debris or soil particles can adhere to the surface of seeds, potentially leading to transmission during planting or germination (Singh et al 2019). Bipolaris oryzae is a seedborne pathogen known as the causal agent of brown spots in rice; it is a hemibiotrophic parasite that can infect and remain dormant in the seeds, and the dormant inoculum will be reactive during seed germination (Sunder et al 2014;Ackaah et al 2023;Thuy et al 2023). So far, there is no report of mycotoxin produced by these pathogens or any other risk related to human health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rhizoctonia solani can survive for extended periods in the soil, and infected plant debris or soil particles can adhere to the surface of seeds, potentially leading to transmission during planting or germination (Singh et al 2019). Bipolaris oryzae is a seedborne pathogen known as the causal agent of brown spots in rice; it is a hemibiotrophic parasite that can infect and remain dormant in the seeds, and the dormant inoculum will be reactive during seed germination (Sunder et al 2014;Ackaah et al 2023;Thuy et al 2023). So far, there is no report of mycotoxin produced by these pathogens or any other risk related to human health.…”
Section: Discussionmentioning
confidence: 99%
“…(Ali et al 2018); A. flavus, Fusarium proliferatum (Phan et al 2021); A. flavus, A. parasiticus (Qi et al 2022); Bipolaris spp., Fusarium spp., Macrophomina phaseolina, Aspergillus spp., Curvularia spp., Botryodiplodia spp. (Ackaah et al 2023); A. niger, Talaromyces pinophilus (Laut et al 2023); and Alternaria alternata, F. moniliforme, Rhizopus nigricans, Helminthosporium oryzae, Pyricularia grisea (Kumar et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Some factors, including warm weather, moist circumstances during rice heading and filling periods, and the relatively higher glume dehiscence rate in hybrid rice seeds, usually lead to a higher chalkiness rate in seed grains and make seeds more susceptible to infection, resulting in poor seed quality [2][3][4]16]. It had been previously reported that the rice seed-infecting pathogens were fungal microorganisms that could invade hulls and kernels, causing seed quality reduction and seedling diseases [17,18]. In our experiment, bacteria could be cultivated on the beef medium, but they could not grow on the rice flour medium, which was similar to endosperm ingredients.…”
Section: Discussionmentioning
confidence: 99%
“…These infections have been shown to signi cantly reduce the quality of rice seeds [8,9]. Depending on the agroecology, disease severity and crop sensitivity, seedborne infections in rice cause yield losses of 50-80 per cent [10,11]. These pathogens promote seed discoloration, seed rot, impaired seed germination and seedling vigour and impede the plant throughout its early development stage.…”
Section: Introductionmentioning
confidence: 99%